Évaluer ex ante la pertinence de projets locaux d’adaptation au changement climatique - Alexandre Magnan (VertigO)
Based upon fieldwork conducted in Mauritius and Rodrigues islands (Indian Ocean), this paper presents a methodology for ex ante assessment of adaptation to climate change projects. It relies on the hypothesis that avoiding environmental, sociocultural and economic maladaptation is a relevant way to start implementing a concrete adaptation process. The paper details the approach adopted on the field. First, and before elaborating “significant criteria” and “relevance indicators” (regarding the long-term adaptation challenge), we developed new bases for facilitating the identification of the study’s targeted population, i.e. the “local vulnerable communities”. To do so, we refined the IPCC definition of vulnerability to make it more operational on the ground. The criteria and indicators are then described, and finally an application of the methodology to concrete projects is proposed. Three major conclusions arise from this empirical experience. (i) Avoiding maladaptation is really a relevant way to start implementing adaptation, as it allows the identification of pragmatic guidelines for today’s action. (ii) The ex ante approach allows gathering projects’ holders and funding agencies thanks to common assessment bases. Yet, such bases are essential pillars for ensuring consistency among scattered adaptation initiatives, while these latter are expected to grow in number in the context of adaptation funds increase. (iii) Ex ante assessments are as necessary as currently dominating ex post assessments, as they contribute upstream and in parallel of projects’ monitoring and efficiency analysis, to the coherence and the optimisation of adaptation endeavours.